Triterpene saponins of the root bark of Olax obtusifolia De Wild. (December 2018) - Pertuit, David; Mitaine-Offer, Anne-Claire; Miyamoto, Tomofumi; Tanaka, Chiaki; Delaude, Clément; Lacaille-Dubois, Marie-Aleth
Graphical abstract: Highlights: Four undescribed triterpene saponins were isolated from Olax obtusifolia . Their structures were determined by spectroscopic methods. A new sugar sequence was described. Abstract: Four undescribed triterpenoid saponins together with five known and oleanolic acid were isolated from root bark of Olax obtusifolia De Wild. Their structures were elucidated by spectroscopic methods including 1D and 2D NMR experiments, in combination with mass spectrometry as 3- O -α-l -rhamnopyranosyl-(1→4)-α-l -rhamnopyranosyl-(1→3)-β-d -glucuronopyranosyloleanolic acid, 3- O -α-l -rhamnopyranosyl-(1→4)-α-l -rhamnopyranosyl-(1→3)-β-d -glucuronopyranosyloleanolic acid 28- O -β-d -glucopyranosyl ester, 3- O -α-l -rhamnopyranosyl-(1→3)-β-d -glucopyranosyl-(1→2)-[β-d -glucopyranosyl-(1→3)]-β-d -glucuronopyranosyloleanolic acid and 3- O -α-l -rhamnopyranosyl-(1→3)-β-d -glucopyranosyl-(1→2)-[β-d -glucopyranosyl-(1→3)]-β-d -glucuronopyranosyloleanolic acid 28- O -β-d -glucopyranosyl ester.